Dimensions Analysis with Qur'anic Qiraat Keywords Using Bibliometric Techniques - Husna Dhiyaul Ilmi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the analysis of the keywords qiraat Al-Qur'an on dimensions. This study uses a bibliometric approach by using mapping analysis keywords using bibliometrics. This study presents the findings of the exploratory research on qiraat Al-Qur'an, as reflected in the research that has been described. This study investigates research fields, research trends, researchers and places of publication related to research on qiraat Al-Qur'an. The results of the research show that the study of qiraat Al-Qur'an is still developing and being studied by many experts.